2021
DOI: 10.53449/ije.v4i2.65
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Adequacy of Aesthetic Nature and Maintenance of School Grounds of the Lagos State Public Schools: A Step Toward Sustainable Development

Abstract: The purpose of this study was to assess the quality of aesthetic nature of school grounds of Lagos state public schools: a step toward sustainable development. Two research questions were raised for the study. Multi-stage sample was used, where forty-six schools were purposively selected from two districts to participate in the study. A descriptive survey design was adopted, and checklist and questionnaire were used to collect data. The reliability coefficients of the instruments were found to be 0.85 and 0.84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In the last decade, a large body of research has focused on analysing the role that school facilities play in the education of students. Previous research has attempted to analyse the extent to which different types of school facilities are available (Akah et al, 2022;Nurabadi et al, 2020;, adequate (Ademiluyi, 2019;Alabi, 2021), functional, accessible (Islam et al, 2020;Oluwalola, 2021), and utilised (Bervell & Arkorful, 2020) for teaching and learning. These studies have revealed different degrees of resource availability in secondary schools.…”
Section: Studies On School Facilitiesmentioning
confidence: 99%
“…In the last decade, a large body of research has focused on analysing the role that school facilities play in the education of students. Previous research has attempted to analyse the extent to which different types of school facilities are available (Akah et al, 2022;Nurabadi et al, 2020;, adequate (Ademiluyi, 2019;Alabi, 2021), functional, accessible (Islam et al, 2020;Oluwalola, 2021), and utilised (Bervell & Arkorful, 2020) for teaching and learning. These studies have revealed different degrees of resource availability in secondary schools.…”
Section: Studies On School Facilitiesmentioning
confidence: 99%